PERANCANGAN BUKU PENGENALAN KALIGRAFI COPPERPLATE DENGAN TEKNIK POINTED PEN - PUTRI NAMIRA ZEIN, Drs. Yusron Wikarya, M.Pd. San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The purpose of this design is designs copperplate calligraphy introductory book with pointed-pen technique. This Introduction Calligraphy of Copperplate book with Pointed-pen technique designed as a design solution for enthusiasts and calligraphy activist in Indonesia who have a problem in accessing the educational sources of Calligraphy Learning, especially in Western Calligraphy. Because this book is designed with the introduction of Indonesia Languages that easy to understand and not too rigid. An Attractive visual display also becomes a design focus in order not to make the reader bored.Data analysis in the design of Calligraphy of Copperplate Book was used by 5W + 1H which the data have been obtained from the observations field such as in Calligraphy Art Communities in Indonesia and Calligraphy writing Classes.This Design produces a Calligraphy of Copperplate Book with Pointed-pen technique as the main media, which also supported by several other media’s, namely: deco-sticker, poster, x-banner, bookmarks, notebooks, Invitation Letter, and Greeting Cards as the main media support and as a promotional medium.Keyword: Calligraphy Book , Copperplate Calligraphy,Pointed-pen technique.